Strategi Pengawas Guru Pendidikan Agama Islam dalam Meningkatkan Tata Kelola Kelas di Sekolah Dasar Negeri - Khadijah Towali; Said Subhan Posangi (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2020)
This study aims to evaluate the Implementation of Supervision of Islamic Religious Education Teachers in improving elementary school classroom management in Marisa District. The research method used is qualitative research, using data collection techniques through observation, interviews, and documentation. The results showed that: 1) The supervisory strategy carried out by all supervisors is to plan and prepare the supervisory apparatus before conducting supervision. The supervisory tools are collected in annual, semester and monthly programs. 2) To get maximum results in supervision, an appropriate approach is needed. The approach in supervision is called technique, both individual and group, each of which has advantages and disadvantages. 3) Overcoming obstacles by collaborating between supervisors and school principals is to set an example or good role model from the principal and senior teachers who are appointed as supervisors, as well as to provide guidance or overall improvement to the professional abilities of teachers by taking into account the accuracy of supervision techniques and principles supervision applied